Staircase-pattern neonatal line in human deciduous teeth is associated with tooth type - Hurnanen J.; Sillanpää M.; Mattila M.; Löyttyniemi E.; Witzel C.; Rautava J. (Elsevier Ltd, 2022)
Objective
The staircase (Sc) pattern enamel microstructure is an expression of an impaired ameloblast function. It has been reported to appear in the neonatal line (NNL), the accentuated stria evincing live birth in deciduous tooth enamel. Our objective was to investigate the prevalence of Sc NNL in deciduous tooth types and its possible association with perinatal circumstances.
Design
Sc in the NNL of 88 teeth, a collection derived from a long-term, prospectively followed population cohort, was recorded with linear polarised transmitted light and analysed for tooth type, duration and mode of delivery, and pain medication used during labour.
Results
Sc prevalence in the NNL differed highly significantly between tooth types (p < 0.0001). An increase in Sc prevalence was significantly associated with an increased ratio of prenatal to total crown enamel (p < 0.001), when buccal and lingual crown walls were analysed separately. No significant association was found between Sc prevalence and duration or mode of delivery or pain-relieving medication (p = 0.57, p = 0.65, p = 0.58, respectively).
Conclusion
This research indicates that the NNL location within tooth crown enamel has a strong impact on microstructural changes along the NNL. Considering our results of Sc prevalence, deciduous canines, having the least Sc appearance, could be used in studies that aim to investigate factors associated with NNL width. In addition, Sc prevalence variation in first deciduous molars might enable to investigation of physiological stressors strong enough to cause ameloblast impairment, such as Sc.